Much a coup about nothing? Was Zimbabwe's 2017 ‘military-assisted change of government' an ‘unconstitutional change of government' as defined by applicable international law? Did the relevant international bodies respond to it in accordance with their own rules? - Hollands, Joshua Charles (Department of Public Law, 2023)
In November 2017, Zimbabwe was characterised by rampant economic issues, endemic corruption and increasing political unrest, especially factional unrest within the ruling ZANUPF party. Then-President Robert Mugabe always seemed too stubborn to ever leave office without a nudge, and in November 2017, that nudge came. Armed members of the Zimbabwean Defence Forces (‘ZDF') took to the streets of Harare in armoured personnel carriers and quickly asserted control over key locations. The ZDF quickly moved to assure civilians that this was ‘not a coup' and that the military was merely purging ‘criminal elements damaging our country' but the ‘President and his family remain safe in their homes.' These events, occurring between 14 and 21 November 2017 led to Mugabe's resignation from the Presidency under concerted pressure. By facilitating Mugabe's resignation, rather than outrightly removing him, the ZDF established a flimsy veneer of legitimacy to the transition of government from Mugabe's leadership to that of his successor, former Vice-President Emmerson D. Mnangagwa (‘ED'). Furthermore, the Zimbabwean Constitutional Court ruled that this transition was ultimately constitutional, as Mugabe resigned ‘voluntarily,' and power was assumed by ED in accordance with the Constitution. Although the Constitutional Court could sanitise the transition domestically, the question of its legal status under international law remains. As a Member State of both the Southern African Development Community (‘SADC') and the African Union (‘AU'), Zimbabwe is legally bound by certain treaty obligations arising from these memberships. The AU in particular usually adopts a strong anti-unconstitutional change of government (‘UCOG') stance and has developed a legal framework for identifying and addressing UCOGs. Thus, although Zimbabwe's Constitutional Court may have effectively whitewashed the change of government, this does not necessarily mean that international law was not breached. If international law has indeed been broken, then it follows that certain consequences should have been attached to the situation. This paper examines the factual background surrounding the 2017 change of government and the relevant legal framework. It assesses whether the actions of the ZDF were in line with the Zimbabwean Constitution, or if the ZDF acted illegally. Should the ZDF's actions in the 2017 transition of government be deemed illegal under the Zimbabwean Constitution, it would mean that the entire transition could amount to an ‘unconstitutional change of government' under AU law, as well as a breach of applicable SADC law. If it is determined that the transition does constitute a UCOG under international law, then both SADC and the AU would have had legal obligations to impose certain consequences on Zimbabwe and the perpetrators of the UCOG. This paper assesses the responses of these two regional bodies to determine whether their responses to the potential UCOG were sufficient under their own rules.